Clinical and financial burden of active lupus in Greece: a nationwide study. (October 2016) - Bertsias, G; Karampli, E; Sidiropoulos, P; Gergianaki, I; Drosos, A; Sakkas, L; Garyfallos, A; Tzioufas, A; Vassilopoulos, D; Tsalapaki, C; Sfikakis, P; Panopoulos, S; et al.
Analyses of the medical and economic burden of chronic disorders such as systemic lupus erythematosus (SLE) are valuable for clinical and health policy decisions. We performed a chart-based review of 215 adult SLE patients with active autoantibody-positive disease at the predefined ratio of 30% severe (involvement of major organs requiring treatment) and 70% non-severe, followed at seven hospital centres in Greece. We reviewed 318 patients consecutively registered over three months (sub-study). Disease activity, organ damage, flares and healthcare resource utilization were recorded. Costs were assessed from the third-party payer perspective. Severe SLE patients had chronic active disease more frequently (22.4% vs 4.7%), higher average SLE disease activity index (SLEDAI) (10.5 vs 6.1) and systemic lupus international collaborating clinics (SLICC) damage index (1.1 vs 0.6) than non-severe patients. The mean annual direct medical cost was €3741 for severe vs €1225 for non-severe patients. Severe flares, active renal disease and organ damage were independent cost predictors. In the sub-study, 19% of unselected patients were classified as severe SLE, and 30% of them had chronic active disease. In conclusion, this is the first study to demonstrate the significant clinical and financial burden of Greek SLE patients with active major organ disease. Among them, 30% display chronic activity, in spite of standard care, which represents a significant unmet medical need.